Membangun Kepercayaan dalam Filantropi Digital: Analisis Tata Kelola (Governance) dan Reputasi Platform Kitabisa - Alif Ramadhana; Marsan Al Muzaki; Sidiq Nurhidayat; Farhan Albari; Gatot Repli Handoko (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid development of digital technology has revolutionized the philanthropic landscape in Indonesia, facilitating public participation through digital crowdfunding platforms. As one of the pioneers in this industry, Kitabisa faces significant challenges in managing public funds accountably amidst the dynamic nature of public opinion on social media. This study analyzes how the implementation of the Governance aspect within the Environmental, Social, and Governance (ESG) framework plays a role in shaping and maintaining Kitabisa's reputation as a trusted crowdfunding platform. Utilizing a media monitoring approach to assess public perception and a literature review to evaluate governance documents, this analysis demonstrates that regulatory compliance, cost transparency, strict campaign verification, and independent financial audits significantly minimize agency problems and increase donation intentions. These findings underscore that robust governance is not merely a compliance instrument, but the fundamental foundation for reputation building and organizational sustainability for philanthropic organizations in the digital era.